Constative speech acts analysis of female student leaders in a Malaysian secondary school / Sharifah Syakila Syed Shaharuddin, Khairon Nisa Shafeei and Asmahanim Mohamad Yusuf - Syed Shaharuddin, Sharifah Syakila; Shafeei, Khairon Nisa; Mohamad Yusuf, Asmahanim (Universiti Teknologi MARA, 2022)
Speech act is a branch of pragmatics in which spoken words or utterances play an important role beyond the function of language in communication. In leadership, speech acts enable leaders to initiate a desirable action or behavior among their followers, and at the same time, convey information more effectively. As such, constative speech acts are commonly used by leaders to describe or depict facts or states of affairs which are either true or false. As to investigate how the different constative speech acts could be used in this context, a qualitative study was conducted with an objective to analyze the constative speech acts of female student leaders in a Malaysian secondary school based on Theory of Speech Acts by Bach & Harnish (1979). Purposive sampling was used to select the research participants and data was gathered from them through a focus group discussion with the researcher. Findings showed that the research participants used various constative speech acts including predictive, assertive, ascriptive, responsive and suggestive in describing the behaviour and characteristics of a good leader. As a conclusion, constative speech acts of the research participants suggest that they could be analytical, firm and sensitive school leaders.